2017
DOI: 10.1186/s12974-017-0823-8
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotrophin regulates microglia-mediated neuroinflammation

Abstract: BackgroundPleiotrophin (PTN) is a cytokine found highly upregulated in the brain in different disorders characterized by overt neuroinflammation such as neurodegenerative diseases, drug addiction, traumatic injury, and ischemia. In the present work, we have explored whether PTN modulates neuroinflammation and if Toll-like receptor 4 (TLR4), crucial in the initiation of an immune response, is involved.MethodsIn immunohistochemistry assays, we studied lipopolysaccharide (LPS, 7.5 mg/kg i.p.)-induced changes in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 48 publications
(65 reference statements)
5
62
0
Order By: Relevance
“…5 e–h). Iba-1 is considered as the activation marker of microglia [ 32 , 33 ]. Immunostaining with anti-Iba1 showed that LPS-treated IL-33 −/− mice had substantially lower numbers of activated microglial cells in cortex sections than LPS-injected WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 e–h). Iba-1 is considered as the activation marker of microglia [ 32 , 33 ]. Immunostaining with anti-Iba1 showed that LPS-treated IL-33 −/− mice had substantially lower numbers of activated microglial cells in cortex sections than LPS-injected WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TAK-242 (TAK) is a novel antagonist of TLR4 and effectively decreases neuroinflammation by its efficacy on blocking TLR4 to bind with its downstream adaptor protein 1 , 20 . In many experimental conditions, inhibition of TLR4 by TAK induced decreases of TLR4 expression 1 , 20 , 21 . The effect of TAK on reducing neuroinflammation in diabetic neuropathy should be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Successful viral infection and disease must overcome the organism immune response. Pleiotrophin (PTN) is a cytokine that modulates inflammation in the CNS 46 . Additionally, PTN negatively regulates protein tyrosine phosphatase zeta (PTPRZ1), which binds to developmental proteins such as beta-catenin 47 .…”
Section: Discussionmentioning
confidence: 99%